(untitled) (Annals of Medical Research, 2021)
Aim: To determine whether the biomicroscopic, topographic and biomechanical properties of the anterior segment and the tear function have changed in Thalassemia Major (TM) patients.Material and Methods: Eighty-eight eyes of patients with TM and 102 eyes of healthy controls paired with age, gender, and spherical equivalent were included in this cross- sectional case-control study. Biomicroscopic, topographic and biomechanical findings of anterior segment and Schirmer test measurements were compared between the two groups.Results: The mean age was found to be 15.11±6.01years in TM group, and 13.83±4.92 years in the control group (p=0.17). In 34 (38.63%) patients with TM, minor peripheral lens opacities were detected. Visual acuity was 20/20 in all patients with lens opacity. The mean iridocorneal angle (ICA) was 44.67±5.86 and the topographic anterior chamber depth (ACD) was 3.65±0.28 mm in the TM patients. Mean ICA was 48.78 ± 6.51 and topographic ACD was 3.76±0.30 mm in the control group (p0.001 and P=0.02 respectively). The mean Schirmer test result was 14.06±4.13 mm in patients with TM and 16.2±3.75 mm in the control group (p=0.001).Conclusion: In contrast to previous literature, we did not found any vision decreasing complications in the TM group. Although peripheral lenticular opacities were detected in some of the patients with TM, none of the patients had an anterior segment finding that could reduce visual acuity. Intraocular lens calculation formulas and surgical technique may be affected due to decreased ICA and ACD values in patients with TM.